The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00436-006-0447-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of cyst differentiation in parasitic protozoa

Abstract: Cysts represent a phase in the life cycle of biphasic parasitic protozoa that allow them to survive under adverse environmental conditions. Two events are required for the morphological differentiation from trophozoite to cyst and from cyst to trophozoite: the encystation and excystation processes. In this paper, we present a review of the ultrastructure of the encystation and excystation processes in Entamoeba invadens, Acanthamoeba castellanii, and Giardia lamblia. The comparative electron microscopical obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Encystation and excystation are two major differentiation steps that are crucial for the completion of the Entamoeba life cycle [27]. The major components of the Entamoeba cyst wall are chitin and chitosan [4].…”
Section: Discussionmentioning
confidence: 99%
“…Encystation and excystation are two major differentiation steps that are crucial for the completion of the Entamoeba life cycle [27]. The major components of the Entamoeba cyst wall are chitin and chitosan [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although cyst viability was not evaluated, the fact that only a few cells formed cyst walls, and these were loose and thin as compared to normal cysts (e.g. Chávez-Munguía et al 2007), even employing optimal microscopy procedures, suggests that the encystment maybe not be effectively producing viable cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their role in the cytolytic effect of this parasite, ultrastructural studies have suggested that EDGs may participate in the excystation process in amebas such as E. invadens, A. castellanii, and Naegleria sp (Chá vez-Munguía et al, 2007). …”
Section: Discussionmentioning
confidence: 98%